1996
DOI: 10.1007/bf02788371
|View full text |Cite
|
Sign up to set email alerts
|

Risk of death from acute pancreatitis

Abstract: Seventeen (8.8%) patients died; mortality showed a decreasing trend over the period of years considered and was correlated, among other things, with necrotizing type of pancreatitis, idiopathic etiology, and shock status on admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(29 citation statements)
references
References 23 publications
2
24
1
2
Order By: Relevance
“…With 5% in our study, we are in this range [1][2][3][4][5][6][7][8][9]16] (table 5). Early mortality has been variously defined as death within 1 week [2-4] or 2 weeks [1,9], five studies having mentioned the exact time of death. With the exception of smaller studies [1,3], we -like others -show that about half of the patients die from acute pancreatitis early and half late, with the first half dying from multiple organ failure and the second from septic complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With 5% in our study, we are in this range [1][2][3][4][5][6][7][8][9]16] (table 5). Early mortality has been variously defined as death within 1 week [2-4] or 2 weeks [1,9], five studies having mentioned the exact time of death. With the exception of smaller studies [1,3], we -like others -show that about half of the patients die from acute pancreatitis early and half late, with the first half dying from multiple organ failure and the second from septic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Early mortality has been variously defined as death within 1 week [2-4] or 2 weeks [1,9], five studies having mentioned the exact time of death. With the exception of smaller studies [1,3], we -like others -show that about half of the patients die from acute pancreatitis early and half late, with the first half dying from multiple organ failure and the second from septic complications. This agrees with a postmortem study showing that 60% of the patients died within one week because of multiple organ failure and 40% of infections later [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heath and Imrie [7] challenged the results, showing that Fan's criteria, known as the Hong Kong criteria, had less predictive value for severity in acute pancreatitis than the Glasgow scores or clinical assessment after 48 h. Heath et al [8] confirmed, showing that the Hong Kong criteria had less predictive value than the Ranson, Glasgow and APACHE II scores. While these studies tested blood glucose on admission against general clinical or biochemical parameters of severity, Talamini et al [19] tested it against mortality. They found that serum glucose 1250 mg/dl (13.88 mmol/l) and a serum creatinine 12 mg/dl (176.8 Ìmol/l) were significant mortality factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, this relatively low mortality rate should be treated with some caution: to start, these medical centers have a long history in the area of research and treatment of acute pancreatitis in Guangdong. On the other hand, there have been large numbers of studies addressing the issue of mortality in acute pancreatitis with various etiologies; in addition, it is said that biliary pancreatitis may have a self-limiting course, while alcoholic pancreatitis is more likely to develop into severe pancreatitis as compared with other etiologies, along with a higher mortality rate [14,15,16]. For this reason, it is of great importance to point out that the predominant etiology of severe acute pancreatitis in this study was biliary tract disease (nearly 50%) which may explain the relatively low mortality rate in severe acute pancreatitis to some extent, suggesting that course and outcome of severe acute pancreatitis are somewhat determined by the underlying etiology which could be further confirmed by multivariate analysis: the biliary etiology served as a protective factor against a poor clinical outcome in patients with severe acute pancreatitis.…”
Section: Discussionmentioning
confidence: 99%